PENGARUH MOTIVASI DAN PELIMPAHAN WEWENANG SEBAGAI VARIABEL MODERATING DALAM HUBUNGAN ANTARA PARTISIPASI ANGGARAN DAN KINERJA MANAJERIAL (STUDI EMPIRIS PADA BEBERAPA PERUSAHAAN MANUFAKTUR DI SEMARANG) - ardiani ika s; ratih murtatiningsih (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2012)
This research purpose is to test empirically the effect of budget participation on manager performance with motivation and responsibility chance as moderating variables. The Respondents of this research are manager, chief executive and supervisor of 6 manufactories corporate in Semarang city, where each manufacture corporate was gave fifteen (15) quesioner directly. Samples was choosed with criterias manager, sub-leader, and supervisors who activaly involve with budget setter and performance evaluation. These results of research suggest that first, budget participation have effect directly on manager performance, second budget participation have effect indirectly on manager performance via motivation and third responsibility chance as moderating variables on the effect budget participation on manager performance.